Administrative Procedures in the Field of Economic Activity - Shevchuk, Oksana; Mentukh, Nataliia (Problems of legality, 2023)
The relevance of the topic is due to the fact that the idea of establishing a free trade area and the single market of the European Union (hereinafter - the EU) between Ukraine and the EU countries in accordance with the Association Agreement with the EU and its Member States, as well as the strict fulfilment of obligations to ensure a zone of economic competition, aims at creating a competitive environment in which business entities enjoy equal competitive conditions and operate in accordance with the same generally accepted rules. The purpose of the study is to analyse various scientific approaches to understanding the administrative procedure, to define its features, and to determine the criteria for classifying the formation and development of administrative procedures in the field of economic activity. The methodological basis of the article is a set of methods and techniques of scientific cognition, both general scientific (logical, historical and legal, systemic analysis, etc.) and special (documentary analysis, comparative legal methods, etc.), which contributes to the achievement of the set goals, ensures a complete and comprehensive understanding of the research topic, scientific reliability and convincing results. The author identifies the characteristic features of administrative procedures: openness, focus on the realisation of public interests, consistent orderliness, normativity, discretion, etc. The criteria for classification of administrative procedures have also been the subject of debate, which eventually led to the development of a significant number of them. The author determines that the content of administrative procedures is the procedure for consideration and resolution of individual administrative cases by administrative authorities and local self-government bodies with a view to protecting the rights and legitimate interests, and also to fulfilling the statutory obligations of all subjects of legal relations. Based on the study, the author formulates conclusions and provides recommendations on the need to amend the Law of Ukraine "On Administrative Procedure" to regulate the mechanism of implementation of the principle of "tacit consent" in legal relations between public authorities and business entities. The introduction of the principle of tacit consent in practice should solve a number of problems in the area of issuing permits. The main ones are: reducing the real time spent by business entities on obtaining permits; limiting the opportunities for abuse by representatives of public authorities related to the delay in the timeframe for issuing pre-trial documents established by the current legislation; business entities avoid unjustified termination or suspension of business activities.